Clinical identification of older adults with hypovitaminosis D: Feasibility, acceptability and accuracy of the 'Vitamin D Status Diagnosticator' in primary care. Issue 197 (March 2020) - Le Moigno, Jean-Michel; Annweiler, Gaëlle; Karras, Spyridon N.; Llewellyn, David J.; Riou, Jérémie; Annweiler, Cédric; ,
Highlights: The VDSD was built to diagnose hypovitaminosis D without blood test. The VDSD was feasible, acceptable and accurate to diagnose hypovitaminosis D in primary care. The VDSD may help GPs in decisions to supplement their older patients. Abstract: The 16-item Vitamin D Status Diagnosticator (VDSD) tool was built to diagnose, without resorting to a blood test, hypovitaminosis D among healthy seniors living at home. The objective of this study was to determine the feasibility of the VDSD by general practitioners (GPs), the acceptability to outpatients, and the diagnostic accuracy of the VDSD in primary care. Ten French GPs were asked from March to May 2015 to perform the VDSD in 30 consecutive outpatients aged ≥70years, living at home, presenting with a history of recurrent falls and/or osteomalacia, and taking no vitamin D supplements. Feasibility was defined as a proportion >70% of VDSD forms fully completed. Completing time, acceptance rate and, when applicable, the reasons for non-completing were assessed, together with the metrological properties of the VDSD to identify hypovitaminosis D ≤75nmol/L, or ≤50nmol/L or ≤25nmol/L. Of the 242 enrolled patients, 218 (mean, 79 ± 6years; 46.3% women) received a VDSD, i.e. completing rate of 90.1%, with an average completing time of 1 min and 48s. The acceptance rate by the patients was 98.8%, and all GPs were satisfied with the tool. The VDSD identified hypovitaminosis D≤75nmol/L with an accuracy of 84.7%, hypovitaminosis D≤50nmol/L with accuracy 75.4%, and hypovitaminosis D≤25nmol/L with accuracy 71.0% (n = 183 assays). The 16-item VDSD can be considered as feasible, acceptable and accurate for diagnosing hypovitaminosis D among older outpatients in primary care without resorting to an expensive blood test.